Pengaruh Supervisi Akademik dan Disiplin Guru terhadap Kinerja Guru SD Negeri Sekecamatan Batanghari Kabupaten Lampung Timur - Sulaimah, Umi; Riyanto, Riyanto; Aminin, Sudirman (Penerbit Goodwood, 2021)
Purpose: This study aimed to determine what percentage of the influence, academic supervision, and discipline of educators on teacher performance. Research methodology: This research used quantitative methods and uses a questionnaire. Results: The results show that (1) there is an effect of X1 against Y (tcount 7,381 > ttable 1,664) and the magnitude of the influence is 41,4%, (2) There is an effect of X2 on Y (tcount 6,441 > ttable 1,664), the effect is 36,4%, (3) multiple regression test, fcount 39,781 > ftable 3,12, which means that there is an effect of academic supervision and teacher discipline together on the performance of SDN teachers in Batanghari sub-district, East Lampung district, amounting to 51.1%. Limitations: The research instrument does not yet have a balanced capacity between the factors that are used as instrument items and the seriousness of filling in the instrument, maybe the answer is not in accordance with the actual conditions. Contribution: The benefits of this research are expected, (1) as a consideration in fostering and developing teacher careers, (2) it can be used as a literature review on improving teacher discipline, (3) for the author, as a condition for completing studies at the Muhammadiyah Metro University Postgraduate Program.